2022
DOI: 10.1186/s12943-022-01575-z
|View full text |Cite
|
Sign up to set email alerts
|

M6A-mediated upregulation of circMDK promotes tumorigenesis and acts as a nanotherapeutic target in hepatocellular carcinoma

Abstract: Background Emerging evidence suggest the critical role of circular RNAs (circRNAs) in disease development especially in various cancers. However, the oncogenic role of circRNAs in hepatocellular carcinoma (HCC) is still largely unknown. Methods RNA sequencing was performed to identify significantly upregulated circRNAs in paired HCC tissues and non-tumor tissues. CCK-8 assay, colony formation, transwell, and xenograft mouse models were used to inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(74 citation statements)
references
References 47 publications
2
72
0
Order By: Relevance
“…m6A modification is a dynamic and reversible methylation modification regulated by the m6A regulators, which is mainly composed of "writers" (METTL3, METTL14), and "erasers" (ALKBH5, FTO), and "readers" (YTHDFs, YTHDCs, IGF2BPs) (10). Increasing studies have confirmed that m6A modification plays an important role in malignant tumors (11,12). For instance, m6A reader YTHDF1 promotes the proliferation, migration, invasion, and cell cycle of hepatocellular carcinoma cells by activating the PI3K/AKT/mTOR signaling pathway (13).…”
Section: Introductionmentioning
confidence: 99%
“…m6A modification is a dynamic and reversible methylation modification regulated by the m6A regulators, which is mainly composed of "writers" (METTL3, METTL14), and "erasers" (ALKBH5, FTO), and "readers" (YTHDFs, YTHDCs, IGF2BPs) (10). Increasing studies have confirmed that m6A modification plays an important role in malignant tumors (11,12). For instance, m6A reader YTHDF1 promotes the proliferation, migration, invasion, and cell cycle of hepatocellular carcinoma cells by activating the PI3K/AKT/mTOR signaling pathway (13).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, researchers have found that m6A-modified ncRNAs are involved in cancer metastasis. For example, m6A-modified circMDK was significantly upregulated in HCC and could promote cancer metastasis in vivo and in vitro [ 122 ]. Therefore, we believe that m6A-modified ncRNAs play a role in the process of cancer metastasis, which suggests that m6A-modified ncRNAs may be used in clinical diagnosis to predict cancer metastasis.…”
Section: Clinical Significance Of M6a-modified Ncrnasmentioning
confidence: 99%
“…Apart from miRNAs, lncRNAs such as H19 and LINC00152 regulate the phosphorylation of AKT to restore erlotinib resistance [ 40 , 41 ]. Furthermore, dysregulated circRNAs serve as miRNA sponges to inactivate PI3K/AKT proteins [ 42 , 43 ], but their mechanisms remain unclear.…”
Section: Mechanisms Of Ncrnas Involved In Egfr Tki Resistancementioning
confidence: 99%